Impact of type 2 diabetes mellitus in the course of acute myocardial infarction of the left ventricle with involvement to the right ventricle - Lozova, Tetiana (ScienceRise: Medical Science, 2018)
The aim. To evaluate the effect of diabetes mellitus (DM) on the clinical course of the acute period of myocardial infarction (MI) of the left ventricle (LV) and the biventricular MI. Materials and methods. 309 patients with Q-MI age 65.5±4.42 years were examined. Patients were divided into 3 groups: the 1st group – 155 patients with MI of the right ventricle (RV) on the background of Q-MI of the posterior wall of the LV, the 2nd group – 53 patients with RV MI due the Q-MI of the LV circular localization, and the 3rd group – 101 patients with Q-MI of the LV posterior wall. Patients with DM were 41 (26.5 %) in the 1st group, 22 (41.5 %) - in the 2nd group, and 26 (25.7 %) patients in the third group. The hospital treatment period was 16.8±2.7 days. Results. Patients with DM in all groups had late admission, usually within 12-24 hours (p <0.05) and after the first day of the MI (p <0.05). Among patients with DM there were more women (p <0.05). The presence of DM was associated with a significantly greater number of ventricular arrhythmias and ventricular fibrillation (p <0.05). The clinical course of the acute MI in patients with DM often complicated of early postinfarction angina (p <0.05), recurrent MI and the LV aneurysms in the 2nd group (p <0.05). The acute heart failure (HF) was more severe in patients with DM with prevalence of the number of cases with Killip II-III (p <0.05) and a higher frequency of cardiogenic shock (p <0.05). Patients with DM had more severe manifestations of chronic HF with greater frequency of the HF IIA, IIB and III NYHA in the total group of patients with MI (p <0.05). Conclusion. The DM in patients with Q-ІМ of the LV and the biventricular MI is accompanied by late admission and is more common in women. The presence of the DM in patients with MI is associated with a higher frequency of ventricular extrasystoles, ventricular tachycardias and ventricular fibrillation, cases of early post-MI angina, the development of recurrent MI and the LV aneurysms. Patients with DM have a high frequency of cardiogenic shock and worse manifestations of acute and chronic HF